Trade Liberalization and Export Variety : A Comparison of Mexico and China - Feenstra, Robert C.; Kee, Hiau Looi (World Bank, Washington, DC, 2017)
The issue of measuring product variety has received relatively little attention due to its inherent difficulty. In the language of index numbers, an expansion in the range of inputs or outputs is a 'new goods' problem: a good that is newly available will have an observed price and quantity, but no corresponding price or quantity the year before. The availability of this new good will yield a welfare gain to consumers, as well as a productivity gain to firms buying the new input. In this paper we show how product variety can be measured in the case of a CES aggregator function. This paper is organized as: after reviewing the literature on the 'new goods' problem in section two, then discuss how to measure export variety in section three. In sections four and five discuss the empirical applications to export variety growth in Mexico and China. Regression results relating trade liberalization to industry export variety are presented in section six, and conclusions are given in section seven.